1993
DOI: 10.1139/x93-252
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of alternatives to herbicides in young conifer plantations in California

Abstract: Escalating controversy on clear-cutting, herbicides, burning, and grazing led to a research program with 40 studies, begun in 1980, that compared most of the vegetation management techniques used for enhancing growth of 1- to 3-year-old conifer seedlings. These include such direct techniques as manual manipulation, mulching, herbicides, and grazing for releasing conifer seedlings from undesirable vegetation, and several silvicultural practices (broadcast burning, group selection, genetically improved seedlings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 0 publications
0
19
1
2
Order By: Relevance
“…By the end of the study 20 plant species had been noted. This number is low relative to that found in other studies (17 to 41 species) in our National Administrative Study in young conifer plantations (McDonald and Fiddler 1993).…”
Section: Discussioncontrasting
confidence: 79%
“…By the end of the study 20 plant species had been noted. This number is low relative to that found in other studies (17 to 41 species) in our National Administrative Study in young conifer plantations (McDonald and Fiddler 1993).…”
Section: Discussioncontrasting
confidence: 79%
“…We found that applying a cutting treatment once, although not as profitable as aerial application of herbicides, is economically viable. However, in some scenarios a single cutting operation may not be sufficient to suppress the competition (MacDonald andFiddler 1993, Heineman et al 2005) and repeated cutting operations are not cost-effective (Comeau and Harper 2009). Although job creation was a major goal of implementing these labour-intensive methods on a large scale, companies now frequently report a shortage of available (willing) workers to carry out mechanical release treatments (Thiffault and Roy 2010;Wyatt et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulated by public opposition to herbicides, research efforts in recent years have sought to develop alternatives to herbicide use, especially aerial forms of application (McDonald and Fiddler 1993, Wagner 1993, Comeau et al 1996. Alternatives to aerially-applied herbicides that have been examined include: ground-applied herbicides (tractor-mounted sprayers, granular formulati&, capsule delivery systems, backpack sprayers), biological control (naturally-occurring organisms such as fungal pathogens or phytotoxins derived from natural sources), prescribed fire, mulches (the spreadmg of materials around desired trees to control competing vegetation), heavy motorized equipment for soil scarification or cutting of vegetation, cover cropping (seeding of desirable non-crop plants to suppress or eliminate unwanted vegetation), grazing animals (primarily sheep), and manual cutting with brushsaws.…”
Section: Introductionmentioning
confidence: 99%